Cinnamon Water Extract: for Lowering High Blood Cholesterol Level of Students and Staff Members of Buraydah College of Pharmacy and Dentistry - Alnemr, Osama; Ahmed, Abdel Hamied; Khan, Mohd. Faiyaz; Akhtar, Juber (Med Phoenix, 2017)
Hyperlipidemia (high level of cholesterol in blood) may have a negative effect on the overall health including hypertension and platelet adhesions. The use of herbal medicine, like consumption of cinnamon in treating and preventing abnormality in lipid metabolism has gained an important attention. In this study, immediate effect of cinnamon extract on blood cholesterol was observed and determined. In this study thirty individuals were participated from Buraydah Private College, Kingdom of Saudi Arabia. Two blood samples were taken from each participant before and after consumption of cinnamon extract in the duration of ten days. Twenty three participants were observed lower blood cholesterol level in compare to before intervention. This study showed that cinnamon have a positive impact on lowering high blood cholesterol. Med Phoenix Vol.2(1) July 2017, 78-80